Comparative Analysis of Student Understanding Levels Using Lecture, Group Discussion and Information Technology- Based Methods of Postpartum Care Education at 'Aisyiyah University Surakarta - Siska Ningtyas Prabasari; Rufidah Maulina; Indrawan Ady Saputro (P3M Universitas 'Aisyiyah Surakarta, 2023)
Postpartum care is one of the most essential subjects in midwifery program which student needs to obtain. This provides students with abilities based on concepts, attitudes, skills and the results of critical thinking as well as an evidence base in practice. This study aims to analyze the comparison of students' understanding levels using information technology-based, lecture and group discussion methods about postpartum care education at 'aisyiyah Surakarta University, especially during the Covid-19 pandemic. The method used was data collection ,form of interviews and questionnaires, related to midwifery care material/competencies using lecture, group discussion and information technology-based methods with a total of 37 students as respondents. Calculation the level of understanding using a Likert Scale, Validity Test (T-count, T-table) and Reliability Test, to find out the results of a comparison of learning models with lecture, group discussion and information technology-based methods. Results : The level of understanding using the lecture method is 81%, 94% in the group discussion method and 100% in information technology-based methods. Conclusion : It can be concluded that the learning model which is most in demand by students and has a strongly high level of comprehension was using information technology-based methods.